A one-dimensional superior logistic map based-image encryption. Issue 3 (3rd October 2022) - Khaitan, Supriya; Sagar, Shrddha; Agarwal, Rashi
The importance of digital media has been increased in this pandemic; the media's security is a huge issue and this led to the development of cryptographic techniques that are secure and fast. Chaos-based image encryption has gained popularity due to its ergodic properties. This paper proposes a 1-dimensional chaotic logistic map cryptography based on superior iterations. Both the real and imaginary parts of the 1-dimensional map are used to generate the chaotic sequence. This chaotic sequence is further mixed with the key. The new sequence is used for scrambling and diffusion of pixel values of an image. The proposed scheme was evaluated using many measures like NPCR, UACI, MSE, PSNR and entropy. The simulation result shows that the cipher image's correlation coefficient is below 0.01. The entropy of the cypher picture is similar to its optimal value of eight; thus, the proposed technique is immune to statistical attack. The demonstrated result of NPCR and UACI shows that the proposed scheme is reliable and robust to differential crypto-analysis attacks. Gaussian and salt and pepper noise are added to the picture, the results show that the proposed scheme is resistant to occlusion attacks.